Identification of wage distribution and wage gaps for purse seine crew members - Roma Yuli Felina Hutapea; Yaser Krisnafi; Rio Ari Simarmata; Djunaidi Djunaidi; Suci Asrina Ikhsan; Ratu Sari Mardiah (Depik, 2024)
Even though the government has established regulations regarding wages, the reality is that the wages received by crew members of fishing vessels are still not in accordance with regulations. Therefore, the purpose of this study is to identify the distribution of wages on purse seine vessels and to find out the gap between the wages received by crew. To achieve this goal, this study uses catch data for three fishing trips from March to May 2022, as well as crew wages from selling catches on the purse seine vessel PT Hasil Laut Sejati. The secondary data used is the productivity of the annual catch of purse seine vessels as well as supporting data from references related to the topics discussed. The data obtained were then analyzed using descriptive analysis, income analysis, and gap analysis. The average wage received by purse seine vessels crew is around Rp. 677,649.67 Rp. 1,190,134.00, the wages received are far below the City Minimum Wage, with a gap of 71.57% - 83.81%. The wages of Batam City purse seine crew are not in accordance with the City Minimum Wage of Batam City. Economic conditions and wages for crew members significantly require crew to continue working, to make ends meet.Keywords:CatchCrewIncome